The Effect of Sports on Psychological and Social Factors in the Elderly Community: A Literature Review - Angela, Christine; Damayanti, Putu Ayu Asri (Sekolah Tinggi Ilmu Kesehatan Kendal, 2024)
Exercise can help to slow the aging process. They are beneficial for psychological and social elements in the elderly society. The elderly will be more fit and cheerful. This literature study will look into the impact of sports on psychological and social elements in the aging process. The search engines were Google Scholar and Researchgate. The keywords were sports, anti-aging, psychological, social, and old. The effect of sport on psychosocial factor in the aging process was studied using 16 papers. The aging process alters body homeostasis, organ systems, and other factors, reducing functional capability from the cellular to the individual level. At the cellular level, beta-endorphin is one of the parameters for athletic effectiveness. Happiness can be provided by beta-endorphins. So, sports has effect for psychologican and social factors in elderly community.